Pengaruh Service Quality , Price Discount dan Store Atmosphere terhadap Impulse Buying - Anisa Rahayu; Dedy Ansari Harahap (Bandung Conference Series: Business and Management, 2023)
Abstract. This study aims to find out how the description of service quality, price discount, store atmosphere and impulse buying at Mall 23 Paskal, and how much influence service quality, price discount, and store atmosphere have on impulse buying. This research is a type of research using quantitative methods. The sampling technique used was nonprobability sampling, namely purposive sampling. The population in this study were consumers who had visited or shopped at Mall 23 Paskal with a sample of 200 respondents. Data analysis used in this research is descriptive analysis and verification using multiple linear regression analysis. f test, t test, and the coefficient of determination.The results of this study indicate that service quality partially has a significant effect on impulse buying, price discounts partially have a significant effect on impulse buying, and store atmosphere partially has a significant effect on impulse buying. Then simultaneously service quality, price discount, and store atmosphere have a significant effect on impulse buying. Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran service quality, price discount, store atmosphere dan impulse buying pada Mall 23 Paskal, serta seberapa besar pengaruh service quality, price discount, dan store atmosphere terhadap impulse buying. Penelitian ini merupakan jenis penelitian dengan mengunakan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobanility sampling yaitu purposive sampling, populasi dalam penelitian ini adalah konsumen yang pernah datang atau berbelanja di Mall 23 Paskal dengan sampel sebanyak 200 responden. Analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif dan verifikatif mengunakan analisis regresi linier bergada. Uji f, Uji t, dan koefisien determinasi. Hasil penelitian ini menujunjukan bahwa service quality secara pasrsial berpengaruh signifikan terhadap impulse buying, price discount secara parsial berpengaruh signifikan terhadap impulse buying, dan store atmosphere secara parsial berpengaruh signifikan terhadap impulse buying. Lalu secara simultan service quality, price discount, dan store atmosphere berpengaruh signifikan terhadap impulse buying.